Characterization of Three-dimensional Jacobi-Poisson Manifolds (European Journal of Pure and Applied Mathematics, 2025)
After a reminder of essential notions concerning Jacobi and Poisson manifolds, we study the relationships between their structures. We also show that for any three-dimensional Jacobi manifold, we can construct a Poisson structure on the same manifold. The paper concludes with some examples of such manifolds.